Quantitative trait locus analysis of seed phosphorus and seed phytate content in a recombinant inbred line population of common bean - Blair, Matthew W.; Sandoval Medina, T.A.; Caldas, GV; Beebe, Stephen E.; Paez, MI (Wiley, 2009)
Phytate is an important antinutritional component of legume seeds, which chelates minerals that are essential to the human diet such as iron and zinc. Phytate levels are often correlated with total seed phosphorus (P). The objective of this research was to evaluate quantitative trait loci (QTL) for seed P and phytate content in an inter-gene pool (G2333 × G19839) recombinant inbred line population of common bean (Phaseolus vulgaris L.) planted at medium and high levels of soil P in randomized complete block experiments. Seed P and phytate content were quantified with spectrophotometric methods based on acid digestion with molybdenum blue and Wade reagents, respectively, and net seed P and net phytate content were calculated on a per-seed basis using seed weights for each experiment. Total seed P varied from 2.8 to 6.1 g kg?1 and phytates varied from 0.29 to 1.78% across fertilization levels. A total of six QTL were found for total or net seed P, while three were found for percentage or net seed phytates. The QTL for seed P and percent phytates were located independently on linkage groups B2 and B11 vs. B6, respectively. Meanwhile, the QTL for net seed P or phytate content were related to seed weight QTL on linkage groups B6, B7, and B10, with one additional net phytate QTL on B5. The results suggest that bean plants can adapt to different initial supplies of P and that seed P and phytate levels in common bean can be modified through plant breeding.